2009
DOI: 10.1002/dneu.20698
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy and development of the nervous system of Nematostella vectensis, an anthozoan cnidarian

Abstract: Nematostella vectensis, an anthozoan cnidarian, whose genome has been sequenced and is suitable for developmental and ecological studies, has a complex neural morphology that is modified during development from the larval to adult form. N. vectensis' nervous system is a diffuse nerve net with both ectodermal sensory and effector cells and endodermal multipolar ganglion cells. This nerve net consists of several distinct neural territories along the oral-aboral axis including the pharyngeal and oral nerve rings,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
292
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(312 citation statements)
references
References 99 publications
10
292
2
Order By: Relevance
“…More recently, GABA immunoreactivity was found in interneurons of the cubozoan jellyfish Carybdea marsupialis (Martin, 2004) and in the ectodermal nerve net of the anthozoan sea anemone Nematostella vectensis (Marlow et al, 2009). GABA immunogold labelling was found in putative neural processes within the neural plexus of the sea anemone Phymactis papillosa (Delgado et al, 2010).…”
Section: Inhibitory Transmitters and Receptors: Gaba And Glycinementioning
confidence: 99%
“…More recently, GABA immunoreactivity was found in interneurons of the cubozoan jellyfish Carybdea marsupialis (Martin, 2004) and in the ectodermal nerve net of the anthozoan sea anemone Nematostella vectensis (Marlow et al, 2009). GABA immunogold labelling was found in putative neural processes within the neural plexus of the sea anemone Phymactis papillosa (Delgado et al, 2010).…”
Section: Inhibitory Transmitters and Receptors: Gaba And Glycinementioning
confidence: 99%
“…N. vectensis constitutes an ectodermal and endodermal nerve net making it a simple and diffuse nervous system that runs throughout the animal's body (Marlow et al, 2009;Nakanishi et al, 2012). Also, recently, the ctenophore (M. leidyi) genome has been sequenced and the organism also possesses a peripheral subepithelial nerve net, neurons and nerves associated with the tentacles (Jager et al, 2011;Richter and King, 2013;Ryan et al, 2013).…”
Section: Reviewmentioning
confidence: 99%
“…Also, the list was cross verified with whole-genome analysis and comparative genomic studies (Anctil, 2009;Moroz et al, 2014;Nikitin, 2014;Putnam et al, 2007;Riesgo et al, 2014;Ryan et al, 2013;Srivastava et al, 2008;Srivastava et al, 2010). Marlow et al, 2009;Nakanishi et al, 2012;Niimura, 2009). These findings provide insights that the prebilaterians exhibit a GPCR-mediated sensory system and suggested that the genetic complexity commonly assumed to have arisen much later in animal evolution is actually an ancestral feature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5A). The emergence of neural structures in metazoans leads to innovation in protein functions (50). Although the origin of nerve cells remains unknown, the Cnidaria, whose name derived from cnidocytes (i.e.…”
Section: In the Cnidarian C Hemisphaerica Two Globins (Chengb1 And mentioning
confidence: 99%